Increasing Interest in Learning in the Pandemic Era with Online Learning Using Powerpoint and Googlemeet Media - Susanti, Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to find out how students' interest in learning in online learning uses powerpoint and google meet media, supporting and inhibiting factors in online learning using powerpoint and google meet media in class III SD Negeri Raci 02 Batangan District, Pati Regency. This research is a qualitative research with descriptive analysis technique. Analysis of research data obtained from the process of searching and compiling systematically, data obtained from observations and interviews, namely data collection, data processing, data presentation, and conclusions. The results showed that interest in learning in the pandemic era with online learning using powerpoint and googlemeet media in class III experienced a good increase. The use of interesting new media fosters a new enthusiasm for students in participating in online learning. Inhibiting factors are time efficiency and effectiveness, lack of parental assistance. Supporting factors are, schools facilitate teachers in schools, and students are given free internet quota